Joint Impact Assessment of CTA's Support to SPC (2004-2014) - Adams, Emil; Caniogo, Vili; Eastgate, Margaret (Technical Centre for Agricultural and Rural Cooperation, 2020)
CTA and SPC have a long working relationship spanning over 15 years. In 2012, CTA commenced an evaluation of the work it had undertaken with several partners such as SPC in the ACP region. This Report documents the findings of an Impact Evaluation of capacity development activities provided by CTA for the Pacific region over the last 10 years through SPC, namely its Land Resources Division (LRD).